The Development of Digital Flipbook as German Language Learning for Senior High School Class XI - Dian Adi Pratiwi; Primardiana Hermilia Wijayati; Rizman Usman (RIRAI Publisher, 2023)
The purpose of this research and development study is to develop a learning media in the form of a Flipbook which will be applied to learning German in Class XI High School. This research adapts the development model of Cennamo and Kalk (2019), which consists of 5 coherent and continuous steps. These steps include (1) Define, (2) Design, (3) Demonstrate, (4) Develop, and (5) Deliver. The score given by the media validator was 80%, the material validator was 77.5%, practitioners were 85%, and trial respondents were 87.2%. Based on predetermined validity criteria, the results show that Flipbook is included in the valid category. This research produces a Flipbook digital book that can be accessed using an internet connection with various gadget devices. Therefore, it can be concluded that the product developed is feasible to be applied in learning German.